2017
DOI: 10.1155/2017/2407037
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Anti-VEGF and Laser Photocoagulation for Diabetic Macular Edema: A Review

Abstract: Diabetic macular edema (DME) is the most common cause of vision loss in diabetic patients. Thirty years ago, the Early Treatment Diabetic Retinopathy Study (ETDRS) demonstrated that focal/grid laser photocoagulation reduces moderate vision loss from DME by 50% or more; thus, macular photocoagulation became the gold standard treatment for DME. However, with the development of anti-VEGF drugs (bevacizumab, ranibizumab, and aflibercept), better outcomes were obtained in terms of visual acuity gain and decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Although anti-VEGF therapy has increasingly become the mainstay of therapy for DR, laser therapy still plays an important role as an adjuvant treatment or rescue therapy. The utility of focal laser as an adjuvant treatment dramatically reduced the frequency of anti-VEGF injections when compared with anti-VEGF treatment alone in DME patients [ 64 ] ( Table 3 ).…”
Section: Current and Novel Treatment Strategies In Drmentioning
confidence: 99%
“…Although anti-VEGF therapy has increasingly become the mainstay of therapy for DR, laser therapy still plays an important role as an adjuvant treatment or rescue therapy. The utility of focal laser as an adjuvant treatment dramatically reduced the frequency of anti-VEGF injections when compared with anti-VEGF treatment alone in DME patients [ 64 ] ( Table 3 ).…”
Section: Current and Novel Treatment Strategies In Drmentioning
confidence: 99%
“…Intravitreal injection of Triamcinolone (in pseudophakic patients only) or anti-VEGF, in particular, have shown to be an alternative to focal or grid laser in the treatment of CSME involving the center of the macula, as these drugs have shown to effective in reducing macular edema and anti-VEGF prevent retinal neovascularization. Also, studies have shown that the combination of laser therapy (focal or grid laser) and intravitreal injection of triamcinolone or anti-VEGF to be very effective in the treatment of CSME than laser therapy alone [8][9][10]. The currently available anti-VEGF are Ranibizumab, Bevacizumab (Avastin), and Pegaptanib.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that in addition to the general disease burden, IVT is a crucial factor of diabetic patients´ quality of life, [ 12 , 20 ] it is reasonable that the value and additional effect of macular laser treatment, either focal or grid, has continuously been investigated until now and controversies still exist. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Conventional MLT monotherapy has been largely replaced by intravitreal injection therapy and several studies tried to evaluate the effect of laser treatment in combination with intravitreal injection therapy. [ 15 ] None of these trials demonstrated a significant effect on visual acuity or a significant reduction of intravitreal injections by adding conventional laser treatment however. [ 8 , 10 ]…”
Section: Introductionmentioning
confidence: 99%